Actualización del tratamiento dicóptico para el paciente ambliope - Gómez Sánchez, Nora Eugenia; Torres Garzón, Leidy Yulieth; Velásquez Puerta, Lisbeth Daniela (Universidad Antonio Nariño, 2023)
In this research work, emphasis is placed on describing and highlighting the latest techniques available for dichoptic treatment to treat amblyopia through the use of different devices.